PENGARUH TOTAL QUALITY MANAGEMENT (TQM), SISTEM PENGUKURAN KINERJA DAN PENGHARGAAN TERHADAP KARYAWAN PADA PT. SINAR GALESONG MANDIRI DI MANADO - Megawati Freli Salendu; Jenny Morasa; Victorina Tirayoh (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
Management performance can be assessed within the administrative management framework in control framework assistance to work on the nature of their performance. For this reason, organizational leaders must be able to address each division to help control the framework of assistance provided by representatives and requests to work on the nature of their performance. The method in this study is the multiple regression analysis method which is used to examine the relationship between the dependent variable and the independent variable in processing the data using a questionnaire with computer assistance through the SPSS 20 program. The population in this study were all 40 employees who worked at PT. Sinar Galesong Mandiri In Manado. The sample in this study is the head of the branch, marketing, sales, spare parts/warehouse, and service. The results of the study show that partially the variables TQM, performance measurement systems, and reward on Employees and reward on Employees have a significant effect while TQM on managerial performance and performance measurement systems on Employees have no significant effect.